2008
DOI: 10.1158/1078-0432.ccr-07-4470
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib-Induced Apoptosis with Limited Clinical Response Is Accompanied by Inhibition of Canonical but not Alternative Nuclear Factor-κB Subunits in Head and Neck Cancer

Abstract: Purpose: Nuclear factor-nB (NF-nB)/REL transcription factors promote cancer cell survival and progression. The canonical (NF-nB1/RELA or cREL) and alternate (NF-nB2/RELB) pathways require the proteasome for cytoplasmic-nuclear translocation, prompting the investigation of bortezomib for cancer therapy. However, limited clinical activity of bortezomib has been observed in many epithelial malignancies, suggesting this could result from incomplete inhibition of NF-nB/ RELs or other prosurvival signal pathways. Ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
77
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(82 citation statements)
references
References 35 publications
4
77
1
Order By: Relevance
“…Bortezomib, a proteasome inhibitor, triggers cell apoptosis by blocking NF-kB activation through IkBa stabilization [63]. However, bortezomib showed limited clinical efficacy in HNSCC because NF-kB activation through the noncanonical pathway remained unchanged [64,65]. Moreover, bortezomib did not impact on other prosurvival pathways driven by STAT3 and ERK1/2 phosphorylation [64].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Bortezomib, a proteasome inhibitor, triggers cell apoptosis by blocking NF-kB activation through IkBa stabilization [63]. However, bortezomib showed limited clinical efficacy in HNSCC because NF-kB activation through the noncanonical pathway remained unchanged [64,65]. Moreover, bortezomib did not impact on other prosurvival pathways driven by STAT3 and ERK1/2 phosphorylation [64].…”
Section: Reviewmentioning
confidence: 99%
“…However, bortezomib showed limited clinical efficacy in HNSCC because NF-kB activation through the noncanonical pathway remained unchanged [64,65]. Moreover, bortezomib did not impact on other prosurvival pathways driven by STAT3 and ERK1/2 phosphorylation [64]. Therefore, the combination of bortezomib with EGFR inhibitors was expected to improve the clinical response.…”
Section: Reviewmentioning
confidence: 99%
“…Hence, it remains elusive as to which stimuli or cellular properties in particular activate potential resistance mechanisms such as induction of immunoproteasome subunits and antiapoptotic UPR pathways in MZ B cells. As noncanonical NF-kB signaling is crucial for MZ B cell development (30), it is possible that activation of this pathway might contribute to the resistance toward bortezomib (31). In this respect it is noteworthy that we have preliminary evidence that noncanonical NF-kB signaling is not inhibited by therapeutic concentrations of bortezomib (D. Mielenz, V.R.…”
Section: Discussionmentioning
confidence: 99%
“…Several in vitro and in vivo studies showed the proteasome inhibitor Bortezomib to effectively inhibit tumour growth, induce apoptosis and lower vessel density in SCCHN (7,(16)(17)(18)(19). Furthermore, Bortezomib led to a sustained but limited response rate in SCCHN patients suffering from tumour recurrence, who underwent radiation therapy combined with Bortezomib (20,21). With regard to these findings, it may be possible that optimisation of Bortezomib efficacy may yield substantial improvement in the therapy of head and neck cancer although the use of Bortezomib in SCCHN is discussed controversially in the literature (22,23).…”
Section: Discussionmentioning
confidence: 99%